Development of the 'Australasian' Woodland at Logan Botanic Garden - Unwin, Barry (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2005)
Logan Botanic Garden, one of the Regional Gardens of the Royal Botanic Garden Edinburgh, has a very mild climate when its northerly latitude is considered. This allows the cultivation of a remarkable range of what would normally be described as exotic, semi hardy plants to be grown. This paper describes the species selection, design and development of a newly refurbished part of the garden, the 'Australasian' woodland.